The effect of fertilizer use on organic melon plants quality - Muhamad, Faozi (Indonesian Journal of Multidisciplinary Science, 2023)
Fertilizer is one of the important factors in plant cultivation, including melon plants. The purpose of this study was to examine the effect of fertilizer use on the quality of organic melon crops. This study used an experimental design. Data in this study were collected through observations of several parameters that measure the quality of melon plant growth results. These parameters include flowering age, harvest age, stem diameter, fruit weight per plant, fruit flesh thickness, and taste test. Data obtained from observations were processed by statistical analysis, including analysis of variance, and further tests were carried out using the Honest Real Difference (BNJ) test at the 5% significance level. The results showed that the interaction between the use of Mutiara NPK fertilizer and Fortune liquid organic fertilizer showed no significant effect on all observation parameters. However, when considered separately, both Mutiara NPK fertilizer and Fortune liquid organic fertilizer had a significant effect on the observation parameters. Pearl NPK fertilizer significantly influenced all observational parameters, including flowering age, harvesting age, stem diameter, widest leaf area, fruit circumference, fruit weight per fruit, and fruit flesh thickness. The best treatment was observed when Pearl NPK was applied at 5 grams per plant. On the other hand, the main factor of using Fortune liquid organic fertilizer affected the parameters of flowering age, harvesting age, and widest leaf area. The best treatment in terms of liquid organic fertilizer was the application of Fortune at 8 ml per liter of water.